2019
DOI: 10.1016/j.bbrc.2018.11.125
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-dependent upregulation of the platelet NLRP3 inflammasome promotes platelet aggregation in a murine model of hindlimb ischemia

Abstract: Platelets play a critical role in the pathophysiology of peripheral arterial disease (PAD). The mechanisms by which muscle ischemia regulates aggregation of platelets are poorly understood. We have recently identified the Nod-like receptor nucleotide-binding domain leucine rich repeat containing protein 3 (NLRP3) expressed by platelets as a critical regulator of platelet activation and aggregation, which may be triggered by activation of toll-like receptor 4 (TLR4). In this study, we performed femoral artery l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Aside from pathogen-related inflammation, platelets are also of relevance in sterile inflammation. With regard to the aforementioned NLRP3 inflammasome, an upregulation of platelet NLRP3 could be observed in a model of hindlimb ischemia in a TLR4dependent manner, ultimately triggering platelet aggregation (96). In another sterile inflammatory condition, in nonalcoholic steatohepatitis, platelet-dependent liver damage was observed (97).…”
Section: Platelets In Inflammation and Infectionmentioning
confidence: 99%
“…Aside from pathogen-related inflammation, platelets are also of relevance in sterile inflammation. With regard to the aforementioned NLRP3 inflammasome, an upregulation of platelet NLRP3 could be observed in a model of hindlimb ischemia in a TLR4dependent manner, ultimately triggering platelet aggregation (96). In another sterile inflammatory condition, in nonalcoholic steatohepatitis, platelet-dependent liver damage was observed (97).…”
Section: Platelets In Inflammation and Infectionmentioning
confidence: 99%
“…Inflammasome assembly and cytokine processing in nucleated cells require 2 signals: the first to induce transcription of the cytokines and inflammasome components and the second to trigger inflammasome activation 83 . Recent reports using different models have shown that platelet inflammasome activation requires TLR4‐mediated signaling, 15,86,87 suggesting a similar 2‐signals response in platelets. The involvement of ATP from dense‐granules in platelet NLRP3 activation is shown to mediate platelet prothrombotic responses through IL‐1β secretion 88 .…”
Section: Pattern Recognition Receptors In Plateletsmentioning
confidence: 99%
“…During dengue infection, platelet inflammasome activation requires reactive oxygen species generated in mitochondria, but not ATP release from granules 50,83 (see Section 6.1). Hence, other evidence regarding NLRP3 and IL‐1β participation in platelet prothrombotic responses have emerged 15,86–90 …”
Section: Pattern Recognition Receptors In Plateletsmentioning
confidence: 99%
See 2 more Smart Citations